On the Interactions Between Narrative Puzzles and Navigation Aids in Open World Games - Haahr, Mads (Springer Verlag, 2023)
Narrative puzzles feature prominently in story-based open world video games where they form part of the progression of a narrative and require exploration and logical and creative thinking to solve. Open world games use navigation aids to help players solve narrative puzzles located across the vast worlds they provide. Narrative puzzles offer designers one of the most interactive methods of conveying a game’s narrative, particularly in the action-adventure focused genre of open-world games. In this paper we discuss the interaction between narrative puzzles and navigation aids in open world games, highlighting in case studies of three different games how the amount of information a navigation aid provides impacts the intricacy and expansiveness of puzzles. Finally, we discuss the design implications of these interactions and suggest potential future analytical uses of the discussed framework.
Lecture Notes in Computer Science (LNCS)
International Conference for Interactive Digital Storytelling (ICIDS)
Keywords: Navigation Aids; Narrative Puzzles; Open World; Video Games; Creative Technologies